The Effect of Work-Life Balance on Turnover Intention with Job Satisfaction as an Intervening Variable - Anya Sekar Ismaulidhia; Roni Kambara; Ana Susi Mulyani (CV. Ulil Albab Corp, 2026)
This study aims to examine the effect of work-life balance on turnover intention, with job satisfaction serving as an intervening variable among millennial employees. A quantitative descriptive approach was employed using a saturated sampling technique, whereby the entire population was included as the research sample. Data were collected through interval-scale questionnaires distributed to 73 millennial employees of PT Nikomas Gemilang, C2B Production Division. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.1.1.2. The findings reveal that work-life balance has a negative and significant effect on turnover intention, indicating that a better balance between work and personal life reduces employees’ intention to leave the organization. Furthermore, work-life balance has a positive and significant effect on job satisfaction, suggesting that employees who experience a healthier balance between their professional and personal lives tend to report higher levels of job satisfaction. However, job satisfaction was found to have no significant effect on turnover intention. In addition, the mediation analysis demonstrates that job satisfaction does not significantly mediate the relationship between work-life balance and turnover intention. These findings indicate that work-life balance plays a more direct and substantial role in reducing turnover intention among millennial employees than through the mechanism of job satisfaction. This study contributes to the human resource management literature by highlighting the importance of organizational policies that support work-life balance as an effective strategy for employee retention and workforce sustainability.